ANNOTATED CHECKLIST OF THE SEED BEETLES (COLEOPTERA: CHRYSOMELIDAE: BRUCHINAE) OF TURKEY (Acta Entomologica Serbica, 2022)
The Bruchinae (Coleoptera: Chrysomelidae) fauna of Turkey is reviewed and an annotated checklist is presented, along with the taxa distribution by the country's provinces. In total, 122 species arranged in 14 genera are listed as the seed beetle fauna of Turkey, which constitutes approximately 25% of the Palaearctic Bruchinae fauna. Additionally, the questionable or problematic records of 11 species are evaluated separately.